Handbook of libraries, archives and information centres in India - Gupta, B. M.; Guha, B.; Rajan, T. N. (New Delhi : Information industry publications, 1987)
THIS VOLUME--LIBRARIES, ARCHIVES AND INFORMATIONAL TECHNOLOGY: AN ANNOTATED BIBLIOGRAPHY, 1970-1990, PART ONE; PART TWO ALSO AVAILABLE IN VOLUME 12 OF SERIES.
Vol 5.
includes index.
Keywords: Archives -- Handbooks, manuals, etc -- India; Data libraries -- Handbooks, manuals, etc -- India